The statutory remedy for unfair prejudice in South African company law - Sibanda, A. (Faculty of Law, University of the Free State, 2013)
The convergence of world economies as a result of globalisation calls for jurisprudential review relating to shareholder rights in various jurisdictions. Most countries, including South Africa, base the protection of minority shareholders on common law as well as “home-grown” legislation. Among its shareholder remedies, South African law provides the statutory remedy for unfair prejudice, also known as the “oppression remedy”. The remedy enables shareholders to seek judicial intervention when their corporate interests are jeopardized often by their majority counterparts. In the past, dissatisfied minority shareholders have utilised this remedy. This article considers whether the development of the remedy from its initial introduction in South African company law has been beneficial to shareholders. The author traces the history of the remedy to the Companies Act 46 of 1926 and its subsequent amendment in the Companies Act 61 of 1973 and Companies Act 71 of 2008, respectively. Recommendations on how the remedy can be further improved from its current form are also made.

Die sameloop van die wêreld se ekonomieë as ‘n gevolg van globalisering het ‘n behoefte geskep vir ‘n juridiese hersiening van die regte van aandeelhouers in verskeie jurisdiksies. Die meeste lande, insluitend Suid-Afrika, baseer die beskerming van minderheidsaandeelhouers op die gemene reg, sowel as “tuisgemaakte” wetgewing. Die Suid-Afrikaanse reg maak, onder ander aandeelhouersremedies, voorsiening vir ‘n statutêre remedie teen onredelike benadeling, ook bekend as die “onderdrukkingsremedie”. Die remedie stel aandeelhouers in staat om geregtelike ingryping te bekom wanneer hul korporatiewe belange benadeel word deur gewoonlik meerderheidsaandeelhouers. In die verlede het minderheidsaandeelhouers hierdie remedie benut. Hierdie artikel ooweeg of die ontwikkeling van hierdie remedie vanaf die aanvanklike inkorporasie daarvan in die Suid-Afrikaanse maatskappyereg aandeelhouers enigsins bevoordeel. Die outeur ondersoek onderskeidelik die geskiedenis van die remedie in die Maatskappywet 46 van 1926 en die daaropvolgende wysiging daarvan in die Maatskappywet 61 van 1973 en die Maatskappywet 71 van 2008. Aanbevelings word ook gemaak oor hoe om die remedie verder te verbeter.
Keywords: Shareholder rights; Minority shareholders; South African company law; Oppression remedy; Unfair prejudice; Companies Act 46 of 1926; Companies Act 61 of 1973; Companies Act 71 of 2008